2015
DOI: 10.1002/jssc.201401275
|View full text |Cite
|
Sign up to set email alerts
|

Screening antiallergic components from Carthamus tinctorius using rat basophilic leukemia 2H3 cell membrane chromatography combined with high‐performance liquid chromatography and tandem mass spectrometry

Abstract: Carthamus tinctorius, used in traditional Chinese medicine, has many pharmacological effects, such as anticoagulant effects, antioxidant effects, antiaging effects, regulation of gene expression, and antitumor effects. However, there is no report on the antiallergic effects of the components in C. tinctorius. In the present study, we investigated the antiallergic components of C. tinctorius and its mechanism of action. A rat basophilic leukemia 2H3/cell membrane chromatography coupled online with high-performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…For the evaluation of the leading compounds in drug discovery, many established analytical methods are widely used. The chemical structures and characteristics of these compounds can be identified with analytical methods such as mass spectrometry and gas chromatography, among others 45 . However, the clinical efficacy or adverse reactions of the agents would remain unexplained without identifying their drug efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the evaluation of the leading compounds in drug discovery, many established analytical methods are widely used. The chemical structures and characteristics of these compounds can be identified with analytical methods such as mass spectrometry and gas chromatography, among others 45 . However, the clinical efficacy or adverse reactions of the agents would remain unexplained without identifying their drug efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical efficacy or adverse reactions of the agents would remain unexplained without identifying their drug efficacy. Many laboratory studies have shown that an evaluation relying on biological functions and roles is indispensable to assess agents, since it can reflect the clinical efficacy and any unknown risks it may pose to patients 45 46 . Therefore, finding an efficient and credible bioanalytical method is sorely needed.…”
Section: Discussionmentioning
confidence: 99%
“…Cell membrane chromatography (CMC) is a biological chromatographic technique that uses cell membranes from tissues or cell lines containing membrane receptors as the chromatographic stationary phase. It is a practical method for screening active components from complex TCMs . To characterize and identify active components interacting with the cell membrane stationary phase, several 2D LC methods have been developed for the rapid investigation of complex TCMs, including heart‐cutting 2D CMC coupled with MS and a comprehensive 2D CMC–MS method .…”
Section: Introductionmentioning
confidence: 99%
“…Cells were cultured in a CF EasyFill‐2 cell factory (Nunc, Denmark) in a humidified atmosphere with 5% CO 2 at 37°C. The RBL‐2H3/CMC column was prepared according to a previously reported procedure . Briefly, RBL‐2H3 cells (1×10 7 ) were harvested and washed three times with physiological saline (pH = 7.4) by centrifugation at 3000 × g for 10 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%